Pavel Șciusev – academician, inginer în construcția podurilor - Anatolie POVESTCA (Dialogica: Revistă de Studii Culturale și Literatură)
This article presents the results of research on unpublished archival documents and those housed in the National Museum of History of Moldova, introduced for the first time into the scientific circuit or addressed by our predecessors in a different context, referencing the life and work of our esteemed compatriot: metric certi- ficates, personal files, correspondence regarding the construction of the engineering system, topographic sketches, photographs, and other important materials. Pavel Shchusev was a renowned bridge construction engineer and a well-known professor at higher education institutions in Moscow. His scientific work, engineering endeavors, and private life are less recognized today. Throughout his lengthy professional career spanning over 50 years, he participated as an engineer in the design, construction, and expert evaluation of over 100 infrastructure projects within the geographical area of the USSR, edited more than 80 studies and specialized articles, and published his monumental work dedicated to bridge construction. He wrote memoirs dedicated to Alexei Shchusev and was an associated member of the Academy of Architecture of the USSR. Pavel Shchusev contributed to the development of the Plan for the Organization and Reconstruction of the city of Chișinău and served as a consultant in the field of engineering for the water supply of the capital from the Dniester River through the dams at Dubăsari and Ghidighici, as well as the accumulation lake in Valea Morilor. He is the author of the unrealized project of the central bridge over the Bîc River.